2021
DOI: 10.1002/jmv.27151
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory viruses in the healthy middle ear and middle ear with otitis media with effusion

Abstract: To investigate the presence of respiratory viruses in the middle ear cavity of the individuals with a healthy middle ear and the children with otitis media with effusion (OME). A total of 72 middle ear samples were collected from 25 children with OME (Group 1) and 47 individuals with no middle ear disease (Group 2). Multiplex realtime polymerase chain reaction was used to investigate the presence of 20 different respiratory viruses. Virus results were compared with bacteriomes of the same populations. At least… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Genomes of respiratory viruses were detected in MEE’s of 65% of the children. Similar studies found lower detection rates (56% and 52%, respectively) ( 6 , 8 ). The amount of amplified genome may have been higher in our study, as other studies applied middle ear washes which may have diluted their specimens.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Genomes of respiratory viruses were detected in MEE’s of 65% of the children. Similar studies found lower detection rates (56% and 52%, respectively) ( 6 , 8 ). The amount of amplified genome may have been higher in our study, as other studies applied middle ear washes which may have diluted their specimens.…”
Section: Discussionsupporting
confidence: 66%
“…Several respiratory viruses have been established as sources of ascending infection from the adenoids and are considered major etiological factors of COME in children (3,4). However, those studies report variable viral detection rates in MEE of children and lack evidence of simultaneous viral occupation of the nasopharynx (5)(6)(7)(8). Furthermore a clear separation of cases with COME from those with AOM or rAOM is missing in most reports, although onset, symptoms, clinical, microbiologic and histopathologic findings vary greatly between the diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Previously we reported, for this same set of samples, that both healthy middle ears and ear with OME have diverse bacteriomes and viromes ( 12 , 14 , 15 ). Here, we hypothesize that the middle ear hosts a mycobiome and the composition of the mycobiome differ according to the health condition of the middle ear.…”
Section: Introductionmentioning
confidence: 84%
“…URIs, including nasopharyngitis, pharyngitis, and tonsillitis, and complications such as otitis media (OM), account for 87.5% of all respiratory tract infections (Nguyen-Van-Tam et al, 2022). OM, a common complication of URIs, often manifests following these infections, illustrating a direct clinical linkage (Durmaz et al, 2021;Principi & Esposito, 2020). OM is predominantly caused by bacteria like S. pneumoniae, H. influenzae, and M. catarrhalis, with viruses also playing a role (Folino et al, 2022;Zahid et al, 2024).…”
Section: Introductionmentioning
confidence: 99%